2019
DOI: 10.1111/syen.12368
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid enrichment of poorly preserved museum specimens refines homology hypotheses in a group of minute litter bugs (Hemiptera: Dipsocoromorpha: Schizopteridae)

Abstract: Although they are a valuable source of specimens, insect natural history collections continue to be under‐utilized in molecular systematics, mostly due to difficulties in obtaining DNA sequences. Old specimens or specimens stored under suboptimal conditions are intractable for traditional Sanger sequencing. In this study we use an inexpensive hybrid capture with in‐house generated baits to retrieve commonly utilized ribosomal and mitochondrial loci from old museum specimens and combine them with a Sanger‐gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…One of these reduced representation methods for isolating homologous loci is sequence capture, also known as targeted capture or hybrid enrichment. This method can isolate many orthologous loci, even from low quality or degraded DNA samples (Hawkins et al, 2016;Knyshov et al, 2019), and has been increasingly used in phylogenetic research of many different groups (Haddad et al, 2018;Courcelle et al, 2019;Liu et al, 2019;Van Dam et al, 2019;Zhang et al, 2019). This technique is particularly useful when working with rare or geographically isolated species represented only by dried specimens in museum collections that would be difficult to collect as fresh specimens.…”
Section: Introductionmentioning
confidence: 99%
“…One of these reduced representation methods for isolating homologous loci is sequence capture, also known as targeted capture or hybrid enrichment. This method can isolate many orthologous loci, even from low quality or degraded DNA samples (Hawkins et al, 2016;Knyshov et al, 2019), and has been increasingly used in phylogenetic research of many different groups (Haddad et al, 2018;Courcelle et al, 2019;Liu et al, 2019;Van Dam et al, 2019;Zhang et al, 2019). This technique is particularly useful when working with rare or geographically isolated species represented only by dried specimens in museum collections that would be difficult to collect as fresh specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Although our recent studies using hybrid capture methods successfully incorporated both ribosomal and mitochondrial sequence data (Knyshov et al, 2019a(Knyshov et al, , 2019b, initial analyses showed that the mitochondrial sequence generated for this dataset contained substantial amounts of missing data and their inclusion in analyses did not positively impact support values. Thus, the final analyses and results presented here are based on ribosomal (Sanger + Illumina datasets) and morphological data.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…We used the protocol of Knyshov et al (2019aKnyshov et al ( , 2019b) to obtain substantially larger molecular datasets for a subset of taxa. Using the primers listed in Knyshov et al (2019aKnyshov et al ( , 2019b, we selected eight specimens with good DNA quality (one dipsocorid, one ceratocombid, two "Ogeriinae" and two Schizopterinae) and used long-range PCR to amplify the nuclear ribosomal operon and the mitochondrion. PCR products were turned into Illumina libraries and sequenced on 5% of a MiSeq V3 lane at IIGB UCR.…”
Section: Hybrid Capture and Illumina Sequencingmentioning
confidence: 99%
See 2 more Smart Citations